Ferrocene Bound Poly(vinyl chloride) as Ion to Electron Transducer in Electrochemical Ion Sensors - Pawlak, Marcin; Grygolowicz-Pawlak, Ewa; Bakker, Eric (American Chemical Society, 2010)
We report here on the synthesis of poly(vinyl chloride) (PVC) covalently modified with ferrocene groups (FcPVC) and the electrochemical behavior of the resulting polymeric membranes in view of designing all solid state voltammetric ion sensors. The Huisgen cycloaddition (“click chemistry”) was found to be a simple and efficient method for ferrocene attachment. A degree of PVC modification with ferrocene groups between 1.9 and 6.1 mol % was achieved. The chemical modification of the PVC backbone does not significantly affect the ion-selective properties (selectivity, mobility, and solvent casting ability) of potentiometric sensing membranes applying this polymer. Importantly, the presence of such ferrocene groups may eliminate the need for an additional redox-active layer between the membrane and the inner electric contact in all solid state sensor designs. Electrochemical doping of this system was studied in a symmetrical sandwich configuration: glassy carbon electrode |FcPVC| glassy carbon electrode. Prior electrochemical doping from aqueous solution, resulting in a partial oxidation of the ferrocene groups, was confirmed to be necessary for the sandwich configuration to pass current effectively.The results suggest that only ~2.3 mol % of the ferrocene groups are electrochemically accessible, likely due to surface confined electrochemical behavior in the polymer. Indeed, cyclic voltammetry of aqueous hexacyanoferrate (III) remains featureless at cathodic potentials (down to −0.5 V). This indicates that the modified membrane is not responsive to redox-active species in the sample solution, making it possible to apply this polymer as a traditional, single membrane. Yet, the redox capacity of the electrode modified with this type of membrane was more than 520 μC considering a 20 mm2 active electrode area, which appears to be sufficient for numerous practical ion voltammetric applications. The electrode was observed to operate reproducibly, with 1% standard deviation, when applying pulsed amperometric techniques.